Mitigation of Salt Stress in Rice through Seed Priming with Regulation of Defense Enzymes - Hemalatha, G.; Renugadevi, J.; Eevera, T. (University of Jaffna, 2018)
In India, rice (Oryza sativa L.) is the major staple food crop providing 43 per cent of calorie requirement for more than 70 per cent of the population. Salinity is one of the major hurdles that cause serious hazards in agriculture thereby limiting agricultural productivity. Various reclamation methods had been followed to alleviate the salinity, among them most successful tool is to increase the productivity which is utilization of tolerance varieties. In addition to that, seed priming is very useful technique to mitigate the effect of salt stress. In this experiment, the rice seeds of salt tolerant (TNAU Rice TRY 3), salt sensitive (ADT (R) 49) and moderately salt tolerant (Co 43) varieties were primed with 0.25% hydrogen peroxide, 75 μM jasmonic acid, 80 μM Sodium nitroprusside (SNP) along with hydropriming and unprimed seeds as control. The performance of primed seeds was assessed under salt affected field. In addition to seed priming, foliar spray with hydrogen peroxide, jasmonic acid and SNP for respective priming treatments were also given to the seedlings on 15th day after sowing (DAS). The field emergence (%) 5th DAS, seedling length (cm), dry matter production (DMP), root volume (ml) and biochemical changes like proline and defense enzymes such as., peroxidase and catalase were observed. The results revealed that priming treatment enhanced the performance of salt sensitive variety in addition to the tolerance and moderately tolerant varieties. The improved performance of primed seeds under salt stress condition may be due to the regulated defense responses leading to systemic tolerance to subsequent salt stress exposure. Hence, from this study it is clearly envisaged that the seed priming with SNP was found to be suitable for enhancing the performance of rice seeds under salinity condition.
Keywords: Defense enzymes; rice; salt stress; sodium nitroprusside